Analysis of Technology Acceptance Model in Understanding of Students Behavior Intention in Use of Sikadu (Dinamika Pendidikan, 2017)
The research aims to know the perception of students of ease use of Sikadu, the perception of students of usefulness use of Sikadu, and the impact of students’ perception of ease and usefulness of Sikadu. The approach of this research used quantitative research with descriptive analysis. Sample was students of Faculty of Economics, class of 2015 and 2016. The results of research indicates that students’ perception of the menu and display existing is easy to use in lecture activities up to the utilization of obtaining learning result information; students’ perception of the menu and display existing in Sikadu is very useful in lecturing activities up to the utilization of learning result information; the ease and usefulness in Sikadu encourages the students to use it although it is still rare used when it is seen from the frequency of using. Students mostly use it at the beginning and end of the semester; and the skill to operate computers. The need and demand to use Sikadu in academic administration becomes the main factors that encourage students to use Sikadu.